Overview Of E-Kianpuas patient Satisfaction on Five DimentionsSERVQUAL in Airputih Dental Health Services - Tasha Citra Purnama; Ratno Adrianto; Irfansyah Baharuddin Pakki (Mulawarman International Conference on Tropical Public Health, 2025)
Background : Quality healthcare services are a top priority in improving community satisfaction as an indicator of public service performance. The Samarinda City Government, through the E- Kianpuas application, has introduced a digital-based public satisfaction survey to assess the quality of health services at community health centers (Puskesmas). This study focuses on dental and oral health services at the Air Putih Health Center, which play a vital role in enhancing community health status Objective : This study aims to describe community satisfaction with the quality of dental and oral health services using the E-Kianpuas application, analyzed through the five SERVQUAL dimensions: Tangibles, Reliability, Responsiveness, Assurance, and Empathy. Research Methods/ Implementation Methods : A quantitative descriptive survey approach was employed, referring to Regulation of the Minister for Administrative and Bureaucratic Reform (Permenpan) No. 14 of 2017. Data were collected from the E-Kianpuas application in 2024 involving 24 respondents aged 18–66 years. Measurements used a 1–4 Likert scale and were analyzed descriptively to calculate averages and convert them into the Community Satisfaction Index (IKM). Results : The overall IKM score was 84.38, categorized as “Good.” The Assurance and Responsiveness dimensions achieved the highest scores, reflecting fast, transparent, and safe services. Meanwhile, Tangibles, Reliability, and Empathy received lower scores, particularly regarding facilities, service time, and staff politeness. Conclusion/Lesson Learned : The E-Kianpuas application effectively evaluates health service quality and supports continuous improvement. Although Air Putih Health Center meets public expectations, enhancing physical facilities, procedural efficiency, and interpersonal communication is essential for optimal service quality.